2020
DOI: 10.1039/d0ra02448a
|View full text |Cite
|
Sign up to set email alerts
|

Stability studies of ZnO and AlN thin film acoustic wave devices in acid and alkali harsh environments

Abstract: Surface acoustic wave (SAW) devices based on piezoelectric thin-films such as ZnO and AlN are widely used in sensing, microfluidics and lab-on-a-chip applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…[35][36] For ZnO NWs, the peaks at 434 cm -1 and 1150 cm -1 are ascribed to the acoustic overtone of E2H and the optical overtone of ZnO, repectively. 37 Results showed that The Raman spectra of the ZnO nanowire/GQDs have the main characteristic peak of GQDs, demonstrating the existence of GQDs. Figure 2(f) shows elements' distribution in the composite layer of ZnO NWs and GQDs, obtained using the EDS.…”
Section: Resultsmentioning
confidence: 92%
“…[35][36] For ZnO NWs, the peaks at 434 cm -1 and 1150 cm -1 are ascribed to the acoustic overtone of E2H and the optical overtone of ZnO, repectively. 37 Results showed that The Raman spectra of the ZnO nanowire/GQDs have the main characteristic peak of GQDs, demonstrating the existence of GQDs. Figure 2(f) shows elements' distribution in the composite layer of ZnO NWs and GQDs, obtained using the EDS.…”
Section: Resultsmentioning
confidence: 92%
“…It creates the acousto-optic effect after interaction with SAW, which is the basic concept of acousto-optic devices [ 47 ]. ZnO, LiNbO 3 , and AlN are used in these structures because of their strong piezoelectric and optical characteristics, as well as the ease with which they are deposited [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. A material’s k 2 is dependent on characteristics such as dielectric, piezoelectric, and elastic properties.…”
Section: Methodsmentioning
confidence: 99%
“…The ZnO-ZnGaON photoanodes showed stable photocurrent and morphology in the amperometric study after 5.5 h at pH 13. In contrast, ZnO photoanodes were fully etched within 5.5 h. Surface acoustic wave (SAW) devices based on ZnO thin film have been investigated toward flexible sensor and microfluidic applications. , Xiong et al demonstrated SAW device operation based on a ZnO thin film in acid and alkali environments . Grain defects in ZnO thin films increase within 45 s in HCl and NaOH solution, resulting in the failure of device operations.…”
Section: Applications Of Zno In Harsh Electronicsmentioning
confidence: 99%
“…166,167 Xiong et al demonstrated SAW device operation based on a ZnO thin film in acid and alkali environments. 167 Grain defects in ZnO thin films increase within 45 s in HCl and NaOH solution, resulting in the failure of device operations.…”
Section: Applications Of Zno In Harsh Electronicsmentioning
confidence: 99%